Language teaching methods of training foreign students-philologists russian phraseological units using audio-visual aids - Мисенёва, В. В. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The objectives, content, didactic principles of using audio-visual aids in foreign audience have been identified and theoretically substantiated in the article. A set of methods, techniques and types of tasks, aimed at mastering Russian phraseological units by foreign students-philologists with the help of visual aids, have been developed by the author.